To find the first term, fourth term, and tenth term of the arithmetic sequence described by the rule A(n) = 5 + (n-1)(1/6), we need to substitute n = 1, n = 4, and n = 10 into the formula.
First term (n = 1):
A(1) = 5 + (1-1)(1/6)
A(1) = 5 + 0
A(1) = 5
The first term of the sequence is 5.
Fourth term (n = 4):
A(4) = 5 + (4-1)(1/6)
A(4) = 5 + 3/6
A(4) = 5 + 1/2
A(4) = 5.5
The fourth term of the sequence is 5.5.
Tenth term (n = 10):
A(10) = 5 + (10-1)(1/6)
A(10) = 5 + 9/6
A(10) = 5 + 3/2
A(10) = 5 + 1.5
A(10) = 6.5
The tenth term of the sequence is 6.5.
Find the first, fourth, and tenth terms of the arithmetic sequence described by the given rule. A (n) = 5 + (n-1) (1/6)
1 answer